Not so much rational but rationalizing: Humans evolved as coherence-seeking, fiction-making animals - YONG, Jose C. (Institutional Knowledge at Singapore Management University, 2021)
The evidence for biased perceptions and judgments in humans coupled with evidence for ecological rationality in nonhuman animals suggest that the claim that humans are the rational animal may be overstated. We instead propose that discussions of human psychology may benefit from viewing ourselves not so much as rational animals but rather as the rationalizing animal. The current article provides evidence that rationalization is unique to humans and argues that rationalization processes (e.g., cognitive dissonance reduction, post hoc justification of choices, confabulation of reasons for moral positions) are aimed at creating the fictions we prefer to believe and maintaining the impression that we are psychologically coherent and rational. Coherence appears to be prioritized at the expense of veridicality, suggesting that distorted perceptions and appraisals can be adaptive for humans—under certain circumstances, we are better off understanding ourselves and reality not so accurately. Rationalization also underlies the various shared beliefs, religions, norms, and ideologies that have enabled humans to organize and coordinate their actions on a grand scale, for better or worse. We conclude with a discussion of the implications of this unique human psychological trait.